2019
DOI: 10.3390/ijms20225526
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: AEG-1/miR-221 Axis Cooperatively Regulates the Progression of Hepatocellular Carcinoma by Targeting PTEN/PI3K/AKT Signaling Pathway

Abstract: Hepatocellular carcinoma (HCC) is the third leading malignancy worldwide, causing mortality in children and adults. AEG-1 is functioned as a scaffold protein for the proper assembly of RNA-induced silencing complex (RISC) to optimize or increase its activity. The increased activity of oncogenic miRNAs leads to the degradation of target tumor suppressor genes. miR-221 is an oncogenic miRNA, that plays a seminal role in carcinogenesis regulation of HCC. However, the molecular mechanism and biological functions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Similarly, our studies revealed that miR‐23a‐3p suppresses U251 cell growth and metastasis by targeting PTEN. In addition, several studies have shown that PTEN is negatively correlated with the high invasiveness of cancer cells (Salvatore et al, 2019), for example, upregulation of PTEN was found to suppress cell migration and invasion by blocking the PI3K/Akt pathway in non‐small cell lung cancer (Liao et al, 2019) and hepatocellular carcinoma (Kannan et al, 2019), and inactivation of MEK1/ERK1 in breast cancer (Liang et al, 2019). The above results suggest that the overexpression of PTEN may be an excellent clinical treatment method for glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our studies revealed that miR‐23a‐3p suppresses U251 cell growth and metastasis by targeting PTEN. In addition, several studies have shown that PTEN is negatively correlated with the high invasiveness of cancer cells (Salvatore et al, 2019), for example, upregulation of PTEN was found to suppress cell migration and invasion by blocking the PI3K/Akt pathway in non‐small cell lung cancer (Liao et al, 2019) and hepatocellular carcinoma (Kannan et al, 2019), and inactivation of MEK1/ERK1 in breast cancer (Liang et al, 2019). The above results suggest that the overexpression of PTEN may be an excellent clinical treatment method for glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Despite developments in liver cancer treatment, with improved surgical techniques and interventional therapies, the 5-year survival rate remains poor and the mortality rate has increased significantly over the past 20 years ( 2 , 3 ). Unlike other organs, the liver displays some potential to regenerate, but the proliferation rate of liver cancer cells is higher compared with that of normal liver cells due to several deregulated signaling pathways during cancer, such as PTEN, PI3K and AKT ( 4 ). Such deregulation occurs throughout all stages of tumor development, which leads to inconsistent and ineffective diagnosis and treatment of liver cancer ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has con rmed low expression of miR-125b in human breast cancer clinical biopsy samples and cell lines [22], whereas miR-125b has been shown to be highly expressed in prostate cancer clinical tissue samples [23]. Although previous studies have reported that miR-221 can act as an oncogene and is involved in the regulation of various cellular processes, including cell differentiation, apoptosis, proliferation, survival, and metastasis in different types of cancers [24,25], in this study, miR-221 may act as a tumor suppressor in NPC.…”
Section: Discussionmentioning
confidence: 99%